The space between us [videorecording (DVD)] - Oldman, Gary; Butterfield, Asa, 1997-; Gugino, Carla, 1971- (Universal Pictures Home Entertainment, 2017)
Sixteen-year-old Gardner Elliot has lived his whole life with a team of scientists on Mars. He's always longed to see Earth to find the father he's never known and to meet a beautiful street-smart girl named Tulsa he's become friends with online. But when his chance finally comes, doctors discover his heart can't withstand the Earth's atmosphere. Eager to find his father, Gardner and Tulsa escape on a cross-country race against time to unravel the mysteries of how he came to be.